Effect of a newly developed pastille on the salivary flow rate in subjects with dry mouth symptoms: a randomized, controlled, monocentric clinical study - S. Bielfeldt; D. Wilhelm; C. Neumeister; U. Schwantes; K. -P. Wilhelm (BMC, 2021)
Abstract Background Xerostomia is associated with several diseases and is a side effect of certain drugs, resulting from reduced saliva secretion. Often, aged and sometimes younger people suffer from (idiopathic) xerostomia. Chewing gum and sucking pastilles may relieve symptoms of xerostomia by increasing the salivary flow rate due to the mechanical effect of sucking and gustatory stimulation. Swallowing problems and the urge to cough or experiencing a tickling sensation in the throat might be alleviated through a reduction in dry mouth symptoms. We investigated whether a pastille containing four polysaccharides increased the salivary flow rate and relieved the symptoms of dry mouth. Methods Participating subjects with xerostomia were randomized into two equally balanced treatment groups. Subjects received the pastille on Day 1 and a control product (Parafilm®) on Day 3, or vice versa. Unstimulated saliva was collected every 2.5 min for 0-10 min. Stimulated saliva was collected after subjects sucked the pastille or the control product. The salivary flow rate was determined gravimetrically, and, in parallel, the feeling of dry mouth was assessed using a visual analog scale. Saliva surface tension was measured in pooled saliva samples (0-5 min of sampling). Additionally, in stimulated saliva from six subjects who sucked the pastille, the presence of the main ingredient-gum arabic-was examined by Raman spectroscopy. Results Chewing the pastille significantly increased the mean salivary flow rate by 8.03 g/10 min compared to the mean changes after chewing the control product (+ 3.71 g/10 min; p < 0.0001). The mean score of dry mouth was significantly alleviated by the pastille (− 19.9 ± 17.9 mm) compared to the control product (− 3.3 ± 18.1 mm). No difference between the two products was seen regarding the saliva surface tension. Gum arabic was present in the saliva of all investigated subjects for up to 10 min after sucking the pastille. Conclusions The pastille was well tolerated and effective in increasing the salivary flow rate and reducing mouth dryness after sucking. These results were in line with the detection of the main ingredient, gum arabic, in saliva for up to 10 min after sucking the pastille. Trial registration German Register Clinical Trials (Deutsches Register Klinische Studien, DRKS) DRKS-ID: DRKS00017393, Registered 29 May 2019, https://www.drks.de/drks_web/navigate.do?navigationId=trial . HTML&TRIAL_ID = DRKS00017393.